Informatization process of wind and solar resource power generation: Empirical abstraction and packing algorithm - Jialin Li & Peng Zhao; Zongtao Yuan; Yingchao Li; Jing Zhang (Trends in Computer Science and Information Technology - Peertechz Publications, 2023)
The development of software tools is critical to meeting the changing needs of the wind and solar resource generation industries. By identifying some of the limitations of existing systems, such as fragmentation in data query and plant management, as well as a lack of data resource management. In response to these issues, it is proposed to use a hybrid deep network model for simulation data to develop a management platform for wind and solar resource observation data. High-quality real-time measurement data and standardized data processing can be collected stably using these tools, which can significantly improve the development efficiency of landscape resource power generation projects and save development costs.